2016
DOI: 10.1038/srep30965
|View full text |Cite
|
Sign up to set email alerts
|

Progress to extinction: increased specialisation causes the demise of animal clades

Abstract: Animal clades tend to follow a predictable path of waxing and waning during their existence, regardless of their total species richness or geographic coverage. Clades begin small and undifferentiated, then expand to a peak in diversity and range, only to shift into a rarely broken decline towards extinction. While this trajectory is now well documented and broadly recognised, the reasons underlying it remain obscure. In particular, it is unknown why clade extinction is universal and occurs with such surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…], or pollinator loss [Steiner and Whitehead ]) or natural (e.g., as documented by the fossil record over 480 million years; Raia et al. ). Defining ecological specialisation can be controversial (Devictor et al.…”
Section: Discussionmentioning
confidence: 99%
“…], or pollinator loss [Steiner and Whitehead ]) or natural (e.g., as documented by the fossil record over 480 million years; Raia et al. ). Defining ecological specialisation can be controversial (Devictor et al.…”
Section: Discussionmentioning
confidence: 99%
“…Slowdown in the rate of lineage accumulation over time has been observed in fossil records [4, 40–42] as well as molecular phylogenies of clades of animals [1,2,4] and plants [43]. Such slowdown could be due to ecological density-dependence, but also to other causes such as adaptive radiation [2,44], protracted speciation [45], incorrect or incomplete phylogenies [41,46,47], niche filling, or other causes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the term density- or diversity- dependence should not be used indiscriminately when diversification slows down, but only when there is evidence of causal density-dependence. Ideally, to distinguish density-dependence from alternative explanations, future analyses of diversification slowdown should take species geographic distribution [42], 2016) and phenotypic differences [22,48] into account [5], and not rely solely on the global numbers of species in a clade.…”
Section: Discussionmentioning
confidence: 99%
“…Two palaeontological studies are consistent with this alternative perspective: Liow () found that species with longer fossil durations have average trait values, while Raia et al . () found that specialization led to increased extinction of entire clades. If it is reasonable to assume that ‘average morphologies’ are groups of species that would contribute little to total TR, and specialization results in groups of species that contribute more to TR, these findings suggest a negative correlation between TR and per capita extinction rate.…”
Section: Evaluating the Arguments For Evolutionary Historymentioning
confidence: 99%